Combinatorial Effect of Magnetic Field and Radiotherapy in PDAC Organoids: A Pilot Study - Luca Nicosia; Filippo Alongi; Silvia Andreani; Ruggero Ruggieri; Borislav Rusev; Beatrice Mantoan; Rita Teresa Lawlor; Antonio Pea; Aldo Scarpa; Linda Agolli; Vincenzo Corbo; Sabrina D’Agosto (Biomedicines, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is highly refractory to systemic treatment, including radiotherapy (RT) either as alone or in combination with chemotherapy. Magnetic resonance (MR)-guided RT is a novel treatment technique which conjugates the high MR imaging contrast resolution to the possibility of re-adapting treatment plan to daily anatomical variations. Magnetic field (MF) might exert a biological effect that could be exploited to enhance radiation effect. The aim of the present study was to lay the preclinical basis of the MF effect by exploring how it modifies the response to radiation in organoid cultures established from PDAC. The short-term effect of radiation, alone or in combination with MF, was evaluated in patient-derived organoids (PDOs) and monolayer cell cultures. Cell viability, apoptotic cell death, and organoid size following exposure to the treatment were evaluated. PDOs demonstrated limited sensitivity at clinically relevant doses of radiation. The combination of radiation and MF demonstrated superior efficacy than monotherapy in almost all the PDOs tested. PDOs treated with combination of radiation and MF were significantly smaller in size and some showed increased cell death as compared to the monotherapy with radiation. Long-time exposure to 1.5T MF can increase the therapeutic efficacy of radiation in PDAC organoids.